Preparation of collagen scaffolds with controlled pore structures and improved mechanical property for cartilage tissue engineering. (September 2013) - Zhang, Qin; Lu, Hongxu; Kawazoe, Naoki; Chen, Guoping
Appropriate pore structures and mechanical properties are required for scaffolds that are used for tissue engineering and regenerative medicine. In this study, pre-prepared ice particulates were used as a porogen material to prepare collagen porous scaffolds with well-controlled pore structures and improved mechanical properties. Porogen ice particulates initiated the formation of interconnected large spherical pores surrounded by small pores. The large spherical pores were well compacted and increased the elastic modulus of the scaffolds. The unique pore structures facilitated cell penetration, resulting in a homogeneous cell distribution throughout the scaffolds. The excellent mechanical properties protected the scaffolds from deformation during cell culturing and implantation. The collagen porous scaffolds facilitated cartilage regeneration when bovine articular chondrocytes were cultured in these scaffolds. The use of pre-prepared ice particulates as a porogen material proved to be a useful method to control the pore structure and improve the mechanical properties of collagen-based porous scaffolds.